Bayesian Modelling of Inflation in Nigeria with Threshold Autoregressive Model - O. Ojo, Oluwadare (Rattanakosin Journal of Science and Technology, 2021)
In this work, we analyze Nigerian inflation rate with Bayesian threshold autoregressive from 1960 to 2019. The threshold models that are special cases where another variable will be the threshold trigger apart from first lag of dependent was considered. This condition may take longer than a period to induce the regime switch. Prior sensitivity analysis was also carried out to know how sensitive the posterior is to changes in prior information while delay parameter that allocates most of the probability through the posterior distribution will be determined. All results from the analysis are robust to changes to in the prior.